New species of Marcetia and Microlicia (Melastomataceae) endemic to the campo rupestre of Chapada Diamantina, Bahia, Brazil - Pacifico, Ricardo; Almeda, Frank (Phytotaxa, 2022)
During recent field expeditions to the Chapada Diamantina (Bahia, Brazil), nine new endemic species of Melastomataceae were collected and are here described and illustrated: Marcetia auricularia, Marcetia santosiae, Marcetia unguiculata, Microlicia ascendens, Microlicia barbata, Microlicia daneui, Microlicia piatensis, Microlicia prostrata, and Microlicia tetramera. We provide photos of living and dry specimens, geographic distribution maps, notes on habitat and phenology for each species, and recommended conservation assessments. Marcetia auricularia, Marcetia unguiculata and Microlicia daneui were collected within a full protection conservation unit, the Chapada Diamantina National Park. Populations of Marcetia santosiae, Microlicia ascendens, Microlicia barbata, Microlicia prostrata, and Microlicia tetramera grow in a sustainable use conservation unit, the Serra do Barbado APA; no protection is afforded to Microlicia piatensis, as it occurs outside all conservation units in the Chapada Diamantina.